Whole-Genome Sequencing Highlights Conservative Genomic Strategies of a Stress-Tolerant, Long-Lived Scleractinian Coral, Porites australiensis Vaughan, 1918. (8th December 2021) - Shinzato, Chuya; Takeuchi, Takeshi; Yoshioka, Yuki; Tada, Ipputa; Kanda, Miyuki; Broussard, Cédric; Iguchi, Akira; Kusakabe, Makoto; Marin, Frédéric; Satoh, Noriyuki; Inoue, Mayuri
Abstract: Massive corals of the genus Porites, common, keystone reef builders in the Indo-Pacific Ocean, are distinguished by their relative stress tolerance and longevity. In order to identify genetic bases of these attributes, we sequenced the complete genome of a massive coral, Porites australiensis . We developed a genome assembly and gene models of comparable quality to those of other coral genomes. Proteome analysis identified 60 Porites skeletal matrix protein genes, all of which show significant similarities to genes from other corals and even to those from a sea anemone, which has no skeleton. Nonetheless, 30% of its skeletal matrix proteins were unique to Porites and were not present in the skeletons of other corals. Comparative genomic analyses showed that genes widely conserved among other organisms are selectively expanded in Porites . Specifically, comparisons of transcriptomic responses of P. australiensis and Acropora digitifera, a stress-sensitive coral, reveal significant differences in regard to genes that respond to increased water temperature, and some of the genes expanded exclusively in Porites may account for the different thermal tolerances of these corals. Taken together, widely shared genes may have given rise to unique biological characteristics of Porites, massive skeletons and stress tolerance.